Fator de crescimento de fibroblasto 18 (FGF18) modula a expressão de CTGF em CCOs e embriões bovinos produzidos in vitro - Silva, Elisabeth Schmidt da (2021)
In 1995, the Hippo pathway was initially discovered in Drosophila melanogaster, and since then several researchers have been trying to better understand this pathway. The Hippo pathway is involved in cell proliferation processes, both in ovarian follicular cells in the early embryonic development. The effectors of this pathway YAP e TAZ act as transcription coactivators of cell proliferation and survival genes such as CTGF and CYR61. However, the fibroblast growth factor also induces CTGF expression. However, recent studies by the group found that fibroblast growth factor 18 (FGF18) is present in the fallopian tube during early embryonic development. This led us to think that FGF18 would have some role during embryonic development. Therefore, the aim of the following study was to determine whether FGF18 modulates the Hippo pathway through the expression of target genes for cell proliferation (CTGF and CYR61) during oocyte maturation and early embryonic development. To acquire the results of the objective, three experiments were carried out, with in vitro maturation (IVM) of cumulus oocyte complexes (COCs) in the first and second experiments, with the addition of FGF18 during IVM, and the structures were collected at different times. In the first experiment, gradual concentrations of FGF18 (0, 10 and 100ng / mL) were added and there was a control group without the addition of FGF18, and 6, 12 and 24 hours of maturation were collected. In the second experiment, a concentration of 100ng / mL of FGF18 was added during IVM, there was a control group and the structures were collected at 0, 3, 6 and 9 hours of maturation. In the experiment, three COCs were put to maturation and were divided into three groups. A group considered a control group in which COCs were matured, with in vitro fertilization (IVF) and then in vitro culture (IVC) without the addition of FGF18. A group in which, during maturation, FGF18 was added only during IVM and afterwards fertilization and culture were carried out in media without the addition of FGF18. In a third group, COCs were put to mature, fertilized and, when put to culture, FGF18 was added in the medium. The genes evaluated in the three experiments were the cell proliferation genes, CTGF and CYR61. In experiment one, which aimed to evaluate the addition of gradual concentrations during maturation, there was an increase (p <0.05) in CTGF gene expression in the group treated with 100ng / mL at 12 hours. In experiment two, in which the objective was to assess the concentration of 100ng / mL, there was a decrease (p <0.05) in the treated group compared to the control group at three hours. And in experiment three in which the objective was to evaluate the addition of FGF18 during embryonic development, there was a statistical difference (p <0.05) in the group treated with FGF18 during IVC. Therefore, we conclude that FGF18 modulates CTGF expression in critical periods of oocyte nuclear maturation, cumulus expansion and early embryonic development in cattle.